A Controlled Carburization Process to Obtain Graphene–Fe3C–Fe Composites. Issue 16 (1st July 2018) - You, Yi; Yoshimura, Masamichi; Cholake, Sagar; Lee, Gwan‐Hyoung; Sahajwalla, Veena; Joshi, Rakesh
Abstract: Significant progresses have been made toward the understanding of graphene growth on metal substrates via chemical vapor deposition method. Cu and Ni are the most studied catalysts for producing high‐quality graphene. Among the transitional metal group, Fe also has the potential as a substrate for growth of graphene. However, the complexity of phase transformation in Fe and the thermodynamically preferable formation of iron carbide at the ambient temperature limit extensive use of Fe for graphene growth. Herein, the concurrent formation of graphene and Fe3 C by optimizing the growth time and cooling rate in graphene growth on Fe substrate is reported. Also, the influence of Fe phases (ferrite and austenite) on the graphene growth is studied. Graphene grain growth on Fe substrate is observed via ultrahigh temperature confocal microscope. The in situ observation confirms that graphene grains are grown around the Fe grain boundaries during the cooling process. The systematic study provides a profound insight into graphene growth on Fe substrate and thus paves a way toward development of graphene‐based steel products for various applications. Abstract : The concurrent formation of graphene and Fe3 C on pure Fe substrate via a controlled carburization process to produce stronger steel is reported. This methodology offers new application of graphene in development of strong composites for real applications. This novel method may have huge impact in steel and other metal industries.